Genotype-first in a cohort of 95 fetuses with multiple congenital abnormalities: when exome sequencing reveals unexpected fetal phenotype-genotype correlations. Issue 6 (30th July 2020) - Lefebvre, Mathilde; Bruel, Ange-Line; Tisserant, Emilie; Bourgon, Nicolas; Duffourd, Yannis; Collardeau-Frachon, Sophie; Attie-Bitach, Tania; Kuentz, Paul; assoum, Mirna; Schaefer, Elise; El Chehadeh, Salima; Antal, Maria Cristina; et al.
Abstract : Purpose: Molecular diagnosis based on singleton exome sequencing (sES) is particularly challenging in fetuses with multiple congenital abnormalities (MCA). Indeed, some studies reveal a diagnostic yield of about 20%, far lower than in live birth individuals showing developmental abnormalities (30%), suggesting that standard analyses, based on the correlation between clinical hallmarks described in postnatal syndromic presentations and genotype, may underestimate the impact of the genetic variants identified in fetal analyses. Methods: We performed sES in 95 fetuses with MCA. Blind to phenotype, we applied a genotype-first approach consisting of combined analyses based on variants annotation and bioinformatics predictions followed by reverse phenotyping. Initially applied to OMIM-morbid genes, analyses were then extended to all genes. We complemented our approach by using reverse phenotyping, variant segregation analysis, bibliographic search and data sharing in order to establish the clinical significance of the prioritised variants. Results: sES rapidly identified causal variant in 24/95 fetuses (25%), variants of unknown significance in OMIM genes in 8/95 fetuses (8%) and six novel candidate genes in 6/95 fetuses (6%). Conclusions: This method, based on a genotype-first approach followed by reverse phenotyping, shed light on unexpected fetal phenotype-genotype correlations, emphasising the relevance of prenatal studies to reveal extreme clinical presentations associated with well-known Mendelian disorders.